Global disease burden linked to diet high in red meat and colorectal cancer from 1990 to 2019 and its prediction up to 2030 - Yang, Xuesong; Wu, Duozhi; Liu, Yanbo; He, Zhigang; Manyande, Anne; Fu, Hongjun; Xiang, Hongbing (Frontiers in Nutrition, 2024)
Numerous studies have already identified an association between excessive consumption of red meat and colorectal cancer (CRC). However, there has been a lack of detailed understanding regarding the disease burden linked to diet high in red meat and CRC. Our objective was to evaluate global, regional, and national mortality rates and disability-adjusted Life years (DALYs) related to this diet. We also considered factors such as sex, age, the socio-demographic index (SDI), and evaluated the cross-national inequalities. Furthermore, we utilized DALYs data from 204 countries and regions to gauge cross-country inequalities of CRC by calculating the slope index of inequality and concentration index as standard indicators of absolute and relative inequalities. Our data was derived from the Global Burden of Disease (GBD) Study 2019. The results show that globally, the age-standardized mortality rate (ASMR) and age-standardized disability adjusted life year rate (ASDR) related to CRC due to diet high in red meat have decreased, with estimated annual percent change (EAPCs) of -0.32% (95% CI -0.37 to -0.28) and -0.18% (95% CI -0.25 to -0.11). Notably, the burden was higher among males and the elderly. The slope index of inequality rose from 22.0 (95% CI 18.1 to 25.9) in 1990 to 32.9 (95% CI 28.3 to 37.5) in 2019 and the concentration index fell from 59.5 (95% CI 46.4 to 72.6) in 1990 to 48.9 (95% CI 34.6 to 63.1) in 2019. Also, according to our projections, global ASDR and ASMR might tend to increase up to 2030. We aim to offer evidence-based guidance for developing effective strategies that can mitigate the elevated CRC burden in certain countries.